Staff Travel Time in Rural- and Urban-Serving Infants and Toddlers With Disabilities (Part C) Programs in Kansas - Tilden, Christopher D.; Kuhn, Nathan C.; Samaddar, Sushmita; McKee, Hilde A.; von Esenwein, Silke A.; Gillam, Rebecca J. (Journal of early intervention, 2025)
Staff travel required to provide home visiting services can be a barrier to quality service provision. This may be of particular concern to rural programs, where the demands of staff travel are often thought to be greater than in urban settings. As part of a statewide needs assessment of the Infants and Toddlers with Disabilities Program in Kansas (Kansas Part C), a time study was conducted to examine travel time in rural and urban programs. While in the field, Part C providers spent 29.9% of their time traveling, over half (51.4%) of their time in direct service, 5.5% preparing documentation, and 2.0% communicating with clients and partners. Travel time did not differ significantly between urban and rural programs. This suggests that caution is warranted when adopting policy approaches, such as funding formula differences, designed to account for assumed (but not documented) differences in rural and urban programs, such as staff travel time.